2021
DOI: 10.20452/pamw.16028
|View full text |Cite
|
Sign up to set email alerts
|

Extremely high mortality in COVID-19 hemodialyzed patients in before anty-SARS-CoV-2 vaccination era. The first large database from Poland

Abstract: This is an Open Access article distributed under the terms of the Creative Commons Attribution-NonCommercial-ShareAlike 4.0 International License (CC BY-NC-SA 4.0), allowing third parties to copy and redistribute the material in any medium or format and to remix, transform, and build upon the material, provided the original work is properly cited, distributed under the same license, and used for noncommercial purposes only.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 17 publications
1
30
0
2
Order By: Relevance
“…According to the latest European Renal Association COVID-19 Database (ERACODA) report, their 28-day probability of death is 25% for all patients, and 33.5% for patients who were admitted into hospitals [5]. In our recent study we showed the extremely high in-hospital mortality of COVID-19 HD patients, with a fatality rate up to 43.81% in subjects over 74 years old [6]. Dialysis patients have a high rate of comorbidities, a high frailty index, and are often elderly and have lowered immunity, which puts them at risk of SARS-CoV-2 infection and a severe course of the disease.…”
Section: Introductionmentioning
confidence: 75%
“…According to the latest European Renal Association COVID-19 Database (ERACODA) report, their 28-day probability of death is 25% for all patients, and 33.5% for patients who were admitted into hospitals [5]. In our recent study we showed the extremely high in-hospital mortality of COVID-19 HD patients, with a fatality rate up to 43.81% in subjects over 74 years old [6]. Dialysis patients have a high rate of comorbidities, a high frailty index, and are often elderly and have lowered immunity, which puts them at risk of SARS-CoV-2 infection and a severe course of the disease.…”
Section: Introductionmentioning
confidence: 75%
“…Ethics approval for the study was obtained at the Medical University of Gdansk (NKBBN/2014/2021). The study is part of the ‘COVID-19 in Nephrology’ (COViNEPH) project focusing on the nephrological aspects of COVID-19, in particular epidemiology, prevention, disease course, and treatment [ 3 , 13 , 14 ].…”
Section: Methodsmentioning
confidence: 99%
“…The dialysis centers became consequently a convenient place for the spread of this disease [ 5 ]. It is therefore no surprise that the COVID-19 epidemic has affected a large proportion of HD patients and the incidence was significantly higher than that of the general population [ 6 , 7 ]. All these factors together put HD patients at a high risk of SARS-CoV-2 infection and a severe course of the disease with fatality rates varying from 16% to 42%.…”
Section: Introductionmentioning
confidence: 99%